The Mn-binding proteins of the photosystem II oxygen-evolving complex are decreased in date palms affected by brittle leaf disease - Marques, Jorge; Durán-Vila, Núria; Daros, José A. (2017)
Brittle leaf disease or maladie des feuilles cassantes (MFC) is a disorder affecting date palms (Phoenix dactylifera L) which after a long declining process eventually leads to the death of the plant. No causal agent for the disease has been found so far but leaflets of affected palms are Mn-deficient despite the existence of adequate exchangeable Mn in the soils in which affected palms grow. The disease is specifically associated with an increase in a series of chloroplastic RNAs. A proteomic analysis of leaflets of affected and unaffected date palms showed differences in quantities of several proteins. Mn-binding PSBO and PSBP proteins, components of the oxygen-evolving complex of photosystem II, were decreased in affected tissue, reinforcing the relation between MFC and Mn deficiency. The quantities of other proteins were increased by disease suggesting a response to stress.